2014
DOI: 10.11646/phytotaxa.184.4.2
|View full text |Cite
|
Sign up to set email alerts
|

Aulacoseira veraluciae sp. nov. (Coscinodiscophyceae, Aulacoseiraceae): a common freshwater diatom from Brazil

Abstract: Examination of samples from different aquatic environments from Brazil revealed the presence of a new Aulacoseira species. Aulacoseira veraluciae Tremarin, Torgan & T. Ludwig is described and illustrated with light and scanning electron microscopy, and its morphology compared with that of similar species, such as A. muzzanensis (Meister) Krammer, A. granulata (Ehrenberg) Simonsen and A. agassizii (Ostenfeld) Simonsen. The new species is characterized mainly by the straight pervalvar rows of areolae, morpho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
3

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
0
7
0
3
Order By: Relevance
“…A new species of Oocystis A.Braun (Ramos et al 2015) was described from the West Atlantic hydrographic region. Three new species of Diatomaceae (one Eunotia and two Aulacoseira) described have wider distribution and span through two or more hydrographic regions (Metzeltin & Tremarin 2011;Tremarin et al 2012;Tremarin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…A new species of Oocystis A.Braun (Ramos et al 2015) was described from the West Atlantic hydrographic region. Three new species of Diatomaceae (one Eunotia and two Aulacoseira) described have wider distribution and span through two or more hydrographic regions (Metzeltin & Tremarin 2011;Tremarin et al 2012;Tremarin et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…):219-230, 15 de março de 2018 Quadro 1. Espécies de fitoplâncton registradas no estado de Mato Grosso do Sul nas duas grandes bacias hidrográficas, Paraguai (1-7) e Paraná (8-12) com suas respectivas referências: 1 (Martins 1980); 2 (Oliveira & Calheiros 2000); 3 (Silva et al 2002); 4 (Domitrovic 2002); 5 (Malone et al 2008); 6 (Vieira et al 2009); 7 (Santos & Sant´Anna 2010); 8 (Train & Rodrigues 1998); 9 (Ferro et al 2008); 10 (Lopes 2009); 11 (Silva 2012); 12 (Tremarin et al 2013); 13 (Tremarin et al 2014). Os números entre parênteses após o nome do gênero são número de espécies.…”
Section: Resultsunclassified
“…No Mato Grosso do Sul os primeiros registros de organismos fi toplanctônicos foram feitos no início do século XX, ainda como estado de Mato Grosso, na cidade de Corumbá (Borges 1903apud Martins 1980. Considerando o período após 1977, quando foi criado o estado de Mato Grosso do Sul , estudos sobre a comunidade fi toplanctônica concentraram-se no Pantanal na década de 1990 e início de 2000 (Espíndola et al 1996, Oliveira & Calheiros 2000, e na bacia do Paraná no século XXI, com estudos em represa urbana (Ferro et al 2008, Lopes, 2009 e Silva 2012) e lagoa rural (Tremarin et al 2013(Tremarin et al , 2014.…”
Section: Introductionunclassified
“…These studies are primarily concentrated on South American lowlands (e.g., Servant-Vildary 1982, Maidana 1996, Sala et al 1999, 2002, Vélez et al 2003, Ribeiro et al 2008, Fontana & Bicudo 2009, Tremarin et al 2011, 2012, 2013, 2014a, 2014b. Some of them showed that detailed analyses can yield new taxa, either by the discovery of novel populations, or by the correction of historical misidentifications (e.g., Tremarin et al 2011Tremarin et al , 2012Tremarin et al , 2014a.…”
Section: Introductionmentioning
confidence: 99%
“…It is also worth noting that the species are those commonly reported from Europe and elsewhere, suggesting that there is little potential for finding novel species in Bolivian water bodies. Since interest in the taxonomy of Aulacoseira is relatively recent in South America (see Tremarin et al 2011Tremarin et al , 2012Tremarin et al , 2013Tremarin et al , 2014aTremarin et al , 2014b) and its taxonomy is now being carefully assessed by detailed comparisons of LM/SEM observations of freshly collected and type material, the assumption that this genus is represented by only a few cosmopolitan species is being challenged.…”
Section: Introductionmentioning
confidence: 99%